The Effect Corporate Social Responsibility (CSR) And Good Corporate Governance (GCG) To Earning Per Share (EPS) - Tri Siwi Nugrahani; Yora Tri Tunggal Dewi (Akmenika: Jurnal Akuntansi dan Manajemen, 2022)
This study examines Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on Earning Per Share (EPS) in Companies Listed in the Jakarta Islamic Index (JII). Corporate Social Responsibility covers the company's activities related to the economy, social, and environment while Good Corporate Governance covers the company's ownership of commissioners, independent commissioners, board of directors, audit committee and audit quality. The research sample was 20 companies at JII during the 2018-2020 period so that the total observations were 60 companies. Data analysis technique with multiple linear regression. The results of the study prove that CSR and GCG in the form of a board of directors have a significant effect on EPS.Keywords: CSR, GCG, EPS